A Design Water Discharge Maxima Forecasting Method Based on Observation Data Using Plotting Position Formulas (MCIT: Proceedings of International scientific and practical conference, 2023)
Plotting position formulas provide a non-parametric means to estimate the observed hydrological data probability distribution. In particular, using a plotting position formula, a plot of the estimated values from a theoretical parametric probability distribution can be compared with the observation data. It allows an examination of the adequacy of the fit provided by parametric probability distributions. However, results of calculating empirical annual probabilities of exceedance observed maxima water discharges show an increase in the divergence between the estimates obtained using the different plotting position formulas in case of more extreme events. Thereby, the choice of a relevant plotting position formula becomes a challenge. Different plotting position formulas may be admissible options. This article shows that the divergence between the plotting position estimates can be extrapolated to predict design maxima water discharges of low exceedance probabilities.